Divulgence of Distribution of Odontogenic Keratocyst Based on Demographic and Radiographic Features: A Retrospective Institutional Study - Nidhi Yadav; Prashanthi Reddy; Ajay Parihar; Sheetal Singar; Varsha; Rashi Mandlik (Wolters Kluwer Medknow Publications, 2023)
Introduction: Odontogenic keratocysts (OKC) is a developmental, slow-growing cyst that illustrates aggressive behaviour, a high recurrence rate, extensive radiologic diversity and variation within age groups and gender. The objective of this study is to evaluate the distribution and radiological traits of patients diagnosed with OKC. Materials and Methods: A cross-sectional retrospective assessment of 40 diagnosed cases of OKC archived at the Government College of Dentistry in Indore was conducted. Demographic information and radiological characteristics of the cases were investigated, sorted, tabulated, and placed through descriptive valuation before being expressed as frequencies and percentages. Results: This study investigated 40 diagnosed OKC cases ranging within the age group of 13 to 63 years (57.5% male and 42.5% female). OKC is more often encountered in the 2nd-3rd decade of life. Depending on the anatomical area, OKC often originates in the posterior mandible, followed by the anterior mandible and maxilla. Concerning radiological characteristics, a unilocular variant was more prevalent (65.0%) than a multilocular. About 97.5% of OKC cases had scalloped and well-corticated borders. Also, the mandibular left third molar was frequently involved (69.2%). Only 15% of OKC cases coexisted with root resorption, 25% with tooth displacement, and 40% with inferior alveolar canal displacement. Conclusion: Our study showed significant disparities in the distribution of OKC among various age groups, genders, and radiological features. Our variables involved in this study were comparable to previous research. Several radiological aspects will aid in treatment strategies, effectiveness, and limiting the recurrence rate. However, a substantial sample size is required to validate these findings.